2002
DOI: 10.1038/nm0502-509
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity due to molecular mimicry as a cause of neurological disease

Abstract: One hypothesis that couples infection with autoimmune disease is molecular mimicry. Molecular mimicry is characterized by an immune response to an environmental agent that cross-reacts with a host antigen, resulting in disease 1,2 . This hypothesis has been implicated in the pathogenesis of diabetes, lupus and multiple sclerosis (MS) 1-4 . There is limited direct evidence linking causative agents with pathogenic immune reactions in these diseases. Our study establishes a clear link between viral infection, aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
226
0
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(241 citation statements)
references
References 24 publications
(3 reference statements)
7
226
0
8
Order By: Relevance
“…Antibodies to neuronal targets have been implicated in the pathology of several neurological disorders including Sydenham's chorea (Kirvan et al, 2003), GuillainBarre syndrome (Ang et al, 2004) and multiple sclerosis (MS) (Gran et al, 1999;Levin et al, 2002). Furthermore, antibodies to the intracellular heterogeneous nuclear ribonuclear protein-A1 have been shown to cause a neurological disease related to MS (Levin et al, 2002), and a recent study has shown an increase in serum levels of the cytokines IL-12 and TNFα in TS .…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to neuronal targets have been implicated in the pathology of several neurological disorders including Sydenham's chorea (Kirvan et al, 2003), GuillainBarre syndrome (Ang et al, 2004) and multiple sclerosis (MS) (Gran et al, 1999;Levin et al, 2002). Furthermore, antibodies to the intracellular heterogeneous nuclear ribonuclear protein-A1 have been shown to cause a neurological disease related to MS (Levin et al, 2002), and a recent study has shown an increase in serum levels of the cytokines IL-12 and TNFα in TS .…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49] There is also evidence for a genetic predisposition as the rates of tic disorders and OCD in first-degree relatives of children in the PANDAS subgroup are higher than those in the general population, and similar to those previously reported for tic disorders and OCD. 50 Several groups have reported the presence of antineuronal antibodies among patients with childhood-onset OCD and/or tic disorders.…”
Section: Pathogenesis Of Pandasmentioning
confidence: 63%
“…Para definir de manera más precisa el proceso autoinmune observado en la paraparesia espástica tropical de la costa pacífica colombiana, es importante determinar el tipo de citocinas producidas diferencialmente por las poblaciones de sus linfocitos T ayudadores (Th (17), quienes identificaron una proteína de aproximadamente 35 kDa en neuronas de corteza cerebral normal humana, la cual reacciona en forma cruzada con un anticuerpo monoclonal para la proteína tax del HTLV-I. Sin embargo, un punto importante de nuestro trabajo es que expande el proceso de reacción cruzada de anticuerpos antitaxp40 no sólo al cerebro sino a regiones de la médula espinal, como la lumbar y la sacra, que jugarían un papel importante en el fisiopatología de la enfermedad en estos pacientes.…”
Section: Discussionunclassified
“…Este proceso, que no es más que la reacción cruzada ocurrida entre los anticuerpos generados como parte de la respuesta inmune a un agente infeccioso y autoantígenos, ha sido confirmado en el complejo sida/demencia (15) y se ha sugerido recientemente para otras enfermedades degenerativas del sistema nervioso central como la esclerosis múltiple (16) y la misma paraparesia espástica tropical (17,18).…”
Section: Autoimmune Syndrome In the Tropical Spastic Paraparesis/myelunclassified